Inferring Interactivity From Gaze Patterns During Triadic Person-Object-Agent Interactions - Jording, Mathis; Hartz, Arne; Bente, Gary; Schulte-Rüther, Martin; Vogeley, Kai (Frontiers in Psychology, 2019)
Observing others’ gaze informs us about relevant matters in the environment. Humans’ sensitivity to gaze cues and our ability to use this information to focus our own attention is crucial to learning, social coordination and survival. Gaze can also be a deliberate social signal which captures and directs the gaze of others towards an object of interest. In the current study, we investigated whether the intention to actively communicate one’s own attentional focus can be inferred from the dynamics of gaze alone. We used a triadic gaze interaction paradigm based on the recently proposed classification of attentional states and respective gaze patterns in person-object-person interactions, the so-called “social gaze space” (SGS). Twenty-eight participants interacted with a computer controlled virtual agent while they assumed to interact with a real human. During the experiment, the virtual agent engaged in various gaze patterns which were determined by the agent’s attentional communicative state, as described by the concept of SGS. After each interaction, participants were asked to judge whether the other person was trying to deliberately interact with them. Results show that participants were able to infer the communicative intention solely from the agent’s gaze behavior. The results substantiate claims about the pivotal role of gaze in social coordination and relationship formation. Our results further reveal that social expectations are reflected in differential responses to the displayed gaze patterns and may be crucial for impression formation during gaze-based interaction. To the best of our knowledge, this is the first study to document the experience of interactivity in continuous and contingent triadic gaze interactions.